Cellular origins and genetic landscape of cutaneous gamma delta T cell lymphomas - Daniels, Jay; Doukas, Peter G.; Escala, Maria E. Martinez; Ringbloom, Kimberly G.; Shih, David J. H.; Yang, Jingyi; Tegtmeyer, Kyle; Park, Joonhee; Thomas, Jane J.; Selli, Mehmet E.; Altunbulakli, Can; Gowthaman, Ragul; et al. (Nature communications, 2020)
Primary cutaneous γδ T cell lymphomas (PCGDTLs) represent a heterogeneous group of uncommon but aggressive cancers. Herein, we perform genome-wide DNA, RNA, and T cell receptor (TCR) sequencing on 29 cutaneous γδ lymphomas. We find that PCGDTLs are not uniformly derived from Vδ2 cells. Instead, the cell-of-origin depends on the tissue compartment from which the lymphomas are derived. Lymphomas arising from the outer layer of skin are derived from Vδ1 cells, the predominant γδ cell in the epidermis and dermis. In contrast, panniculitic lymphomas arise from Vδ2 cells, the predominant γδ T cell in the fat. We also show that TCR chain usage is non-random, suggesting common antigens for Vδ1 and Vδ2 lymphomas respectively. In addition, Vδ1 and Vδ2 PCGDTLs harbor similar genomic landscapes with potentially targetable oncogenic mutations in the JAK/STAT, MAPK, MYC, and chromatin modification pathways. Collectively, these findings suggest a paradigm for classifying, staging, and treating these diseases. Cutaneous gamma-delta T cell lymphomas are rare but aggressive cancers. Here, by DNA, RNA and T cell receptor sequencing, the authors elucidate the molecular ontogeny by revising the cell of origin and identifying potentially targetable mutations.